The Effect Of Explosive Power Limb Muscle And Waist Flexibility And Confidence On Football Shooting Skills (Case Study On 5 SSB In Bengkulu City) - Dolly Apriansyah (Hanoman Journal: Physical Education and Sport, 2021)
This study aims to determine the explosive power of leg muscles and waist flexibility as well as confidence in soccer shooting skills. The research method used in this study is a survey method with measurement and test techniques, while the analysis technique uses a path analysis approach, namely research that will examine or analyze the relationship between research variables, and measure the direct and indirect effects of one variable on other variables. The results of the research on (X1) obtained the lowest score of 1.99 meters, the highest score of 2.54 meters so that the range was 0.55 meters. From the statistical calculation, the average value (X) is 2.30 meters, the standard deviation (s) is 0.16 and the variance is 0.02.